The challenges of implementing cultural-based teaching in remedial education: analyses and recommendations - Salehuddin Al As Anuas; Nurfaradilla Mohamad Nasri; Aliza Alias (International Journal of Evaluation and Research in Education (IJERE), 2024)
In remedial education, teachers play a crucial role in ensuring students from diverse backgrounds master language literacy skills. The current implementation of cultural-based teaching is perceived as an effort to assist remedial students from diverse backgrounds and cultures to learn effectively. The study aims to analyze teachers’ perceptions of challenges in implementing cultural-based teaching in remedial education for language literacy. The study employed a quantitative approach by distributing questionnaires to 252 remedial teachers recruited randomly from primary schools in the Malaysian middle-state zone. The collected data were evaluated descriptively, and the results revealed that these teachers experienced challenges in four areas, namely teaching resources, remedial curricula, teacher knowledge, and time allocation. Moreover, the findings demonstrated that demographic factors, such as gender, school location, and years of teaching experience, did not produce significant impacts on the aforementioned challenges. Simultaneously, this study explored teachers’ perceptions of recommending culturally responsive teaching approaches in remedial education as an alternative to the current cultural-based teaching methodology.